Sosialisasi Pelayanan Prima Dalam Permohonan Paspor Republik Indonesia Di Kantor Imigrasi Kelas I TPI Bengkulu - Retno Sari, Dinda Ayu; Maulidia, Hanifa; Priyatno, Mas Budi; Jannah, Rahmawati Nurul; Utami, Devina Yuka (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2022)
TPI Bengkulu Class I Immigration Office as a public service sector in the field of immigration strives to provide excellent service facilities for every community, especially applicants Republic of Indonesia passport. The services provided by employees are in accordance with standard operating procedures for services, but there are still applicants whose needs have not been met. So that it is still necessary to increase employee competence through socialization of excellent service. The existence of various backgrounds of applicants both in terms of culture, education, customs and others causes complaints from applicants for passports of the Republic of Indonesia to still exist. However, the percentage is relatively small compared to the total number of passport applicants at the Immigration Office Class I TPI Bengkulu. This study aims to determine the process of implementing excellent service socialization for employees at the Immigration Office Class I TPI Bengkulu. The type of research method used is descriptive qualitative, with data collection techniques through observation, interviews and documentation. The results of the study show that the socialization of excellent service at the Immigration Office Class I TPI Bengkulu is secondary socialization according to Berger and Luckman (2019) which has been well implemented at the Immigration Office Class I TPI Bengkulu by using 6 indicators according to Chao (1994), namely performance proficiency), people, politics, language, organizational goals and values, and history (history).